The complete mitochondrial genome sequence of Sinogastromyzon sichangensis (Cypriniformes, Balitoridae). (2nd November 2015) - Yu, Dan; He, Rong; Tang, Qiongying
Abstract: Sinogastromyzon sichangensis, belonging to the family Balitoridae in Cypriniformes, is endemic to the Upper Yangtze River and the Qing River. In this study, the complete mitochondrial genome of S. sichangensis was sequenced with its structure analyzed. The mitochondrial genome of S. sichangensis is similar to those of the typical vertebrates, 16, 567 bp in length, including 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes and one non-coding control region (D-loop). The D-loop of S. sichangensis was characterized by one termination-associated sequence and seven conserved sequence blocks (CSB-F, CSB-E, CSB-D, CSB-B and CSB I-III). The mitogenome sequence of S. sichangensis could contribute to estimate the phylogenetic relationship of the Balitoridae. Further investigations with more Sinogastromyzon species and other balitorid fishes included should be performed to better understand the evolutionary history of this unique group of fishes which can successfully adapt to mountain torrents.